2018
DOI: 10.15407/ufm.19.02.195
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Structure and Surface Properties of Hypoeutectic Silumin by Intense Pulse Electron Beams

Abstract: MoDification of strUctUre anD sUrface ProPerties of hyPoeUtectic silUMin By intense PUlse electron BeaMs Methods of contemporary physical materials science are applied for the analysis of structural and phase states, tribological and mechanical properties of hypoeutectic silumin treated by electron beams with parameters as follow: energy density-10-35 j/cm 2 , pulse duration-10 µs, number of pulses-3, pulse-repetition frequency-0.3 Hz. The initial structure of silumin comprises grains of aluminiumbased solid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Recently, high-current pulsed electron beam technology (HCPEB), a surface modification micro-structure optimization technology, has attracted considerable attention because it is not affected by ion impurities, as ion beam technology is, and it has a much higher energy efficiency than the laser beam [14][15][16]. Ivanov et al used a highcurrent pulsed electron beam to process hypoeutectic Al-Si alloy and found that because of the presence of the submicron Al-based solid solution formed by HCPEB irradiation and nano-scale structure at the grain boundary, the hardness of the surface layer increased by 3.8-4.2 times [17]. During the HCPEB treatment process, the surface can quickly melt and solidify in a short time (the cooling rate is as high as 10 7 -10 9 K/s).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high-current pulsed electron beam technology (HCPEB), a surface modification micro-structure optimization technology, has attracted considerable attention because it is not affected by ion impurities, as ion beam technology is, and it has a much higher energy efficiency than the laser beam [14][15][16]. Ivanov et al used a highcurrent pulsed electron beam to process hypoeutectic Al-Si alloy and found that because of the presence of the submicron Al-based solid solution formed by HCPEB irradiation and nano-scale structure at the grain boundary, the hardness of the surface layer increased by 3.8-4.2 times [17]. During the HCPEB treatment process, the surface can quickly melt and solidify in a short time (the cooling rate is as high as 10 7 -10 9 K/s).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the comprehensive properties of 7075 aluminum alloy joints, post-weld treatment is an ideal and popular method [ 12 , 13 , 14 ]. Many post-weld treatment methods exist for welded joints, such as electron beam treatment [ 15 , 16 ], heat treatment and mechanical treatment. However, welded joints of 7075 aluminum alloy normally undergo post-weld heat and mechanical treatments, of which the heat treatment is usually aging treatment [ 17 , 18 ], and the mechanical treatment usually ultrasonic impact treatment (UIT) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These sets allow for rates of change and interactions between variables, such as temperature, density, or pressure. This methodology therefore has wide applications such as design optimization in mechanical engineering [1], [2], [3], health engineering [4], materials engineering [5], and applied physics [6], [7]. Box and Behnken in [8] introduced a class of three-level second-order designs (SODs) for fitting second-order response surfaces over a spherical region.…”
Section: Introductionmentioning
confidence: 99%